2012
DOI: 10.1007/s00405-012-2028-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of laryngopharyngeal reflux in the English population

Abstract: Although symptoms of laryngopharyngeal reflux (LPR) symptoms are commonly seen in the ENT clinic, their aetiology and prevalence in the population remain unknown. Lifestyle changes have been seen to be effective in symptom relief. We aimed to establish the prevalence of these symptoms and identify any associated factors. Pseudo-random sampling was performed on 2,000 adults that were sent a validated questionnaire containing the Reflux Symptom Index (RSI) and questions on their health and lifestyle. 45.8 % of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
80
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 20 publications
5
80
0
4
Order By: Relevance
“…Improving gastric emptying and oesophageal clearance reduces proximal weakly acidic reflux, which probably causes both refractory GORD and LPR. Contrary to the Montreal consensus guidelines for GORD, LPR clearly does occur in the absence of typical reflux symptoms and is frequently associated with IBS or other functional colonic symptoms as reported in prior studies . GORD has always been a motility disorder, not a disease of excess acid production.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Improving gastric emptying and oesophageal clearance reduces proximal weakly acidic reflux, which probably causes both refractory GORD and LPR. Contrary to the Montreal consensus guidelines for GORD, LPR clearly does occur in the absence of typical reflux symptoms and is frequently associated with IBS or other functional colonic symptoms as reported in prior studies . GORD has always been a motility disorder, not a disease of excess acid production.…”
Section: Discussionmentioning
confidence: 64%
“…LPR has been associated with IBS and a large British community study confirmed that IBS was a strong predictor of chronic cough with a higher odds ratio than both regurgitation and heartburn . Past GI physiological studies have demonstrated that colonic or rectal distension reduces small intestinal, gastric and oesophageal tone and motility, which is reversible with decompression .…”
Section: Introductionmentioning
confidence: 99%
“…Aerodigestive tract disorders attributed to reflux of gastric content into the pharynx remain a diagnostic and therapeutic challenge. These disorders include a number of pulmonary, pharyngeal, and laryngeal abnormalities ranging from aspiration pneumonia, pulmonary fibrosis, asthma, and chronic cough to benign inflammatory lesions of the larynx, pharynx, sinuses, dental erosion, and recurrent otitis media, with an estimated prevalence of 20% to 30% . The incompetence of the upper esophageal sphincter (UES) to prevent passage of esophageal refluxate into the pharynx and occurrence of esophagopharyngeal reflux (EPR) is fundamental to development of the above disorders …”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported that 10% of patients presenting have LPR 18. Kamani et al19 estimated that the prevalence of LPR symptoms in the UK population was 34.4%. Globus sensation, throat clearing, cough, and other nonspecific symptoms are different presentations that may be related to LPR.…”
Section: Discussionmentioning
confidence: 99%